Local Anesthetic Injection Speed and Common Peroneal Nerve Block Duration: A Randomized Controlled Trial in Healthy Volunteers. Issue 5 (July 2018) - Madsen, Mikkel Herold; Christiansen, Claus B.; Rothe, Christian; Andreasen, Asger M.; Lundstrøm, Lars H.; Lange, Kai H.W.
Abstract : Background and Objectives: The speed of local anesthetic (LA) injections in peripheral regional anesthesia ranges from slow continuous infusions (3–12 mL/h) to rapid manual injections (>7500 mL/h). Optimizing injection speed could augment the spread of LA toward the targeted nerves and influence nerve block characteristics. The objective of this study was to investigate whether injection speed of a single dose of LA affects peripheral nerve block duration. Methods: After approval from the Danish Regional Scientific Ethics Committee, we enrolled 60 healthy adult volunteers. We used an ultrasound-guided catheter-based technique to perform a common peroneal nerve block. Participants were randomized to receive 4.0 mL of ropivacaine 0.2% with 1 of 5 injection speeds: 12, 60, 300, 600, or 1800 mL/h. Investigators and participants were blinded to group assignment and intervention. Primary outcome was duration of sensory nerve block defined by insensitivity toward cold. Secondary outcomes were duration of motor nerve block, time to onset of sensory nerve block, and grades of sensory and motor nerve block. Intergroup differences were tested by one-way analysis of variance. Results: We found no differences in sensory block duration between the 5 groups. Durations were median [range]: 11 [6–14], 12 [9–14], 10.5 [2–15], 11 [8–17], and 12 [9–18] hours, respectively ( P = 0.294). In addition, we found no differences in secondary outcomes. Conclusions: Injection speed of LA in the range of 12 to 1800 mL/h did not affect common peroneal nerve block duration. Clinical Trial Registration: This study was registered at ClinicalTrials.gov, identifier NCT02801799.